Pick the plot - Riley, James, 1977- (Riley, James, 1977- Story thieves., 2017)
Owen is trapped in a time travel plot-your-own-adventure book, controlled by the reader, and a bizarre fellow prisoner, Kara Dox, might be his only hope for escaping to save Bethany.